2015
DOI: 10.2147/ott.s78974
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile analysis of colorectal cancer to investigate potential mechanisms using bioinformatics

Abstract: This study aimed to explore the underlying molecular mechanisms of colorectal cancer (CRC) using bioinformatics analysis. Using GSE4107 datasets downloaded from the Gene Expression Omnibus, the differentially expressed genes (DEGs) were screened by comparing the RNA expression from the colonic mucosa between 12 CRC patients and ten healthy controls using a paired t-test. The Gene Ontology (GO) functional and pathway enrichment analyses of DEGs were performed using the Database for Annotation, Visualization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Calcium ions play a vital role in muscle contraction, neuronal transmission, cell motility, cell growth or proliferation [ 24 27 ]. It has been reported that calcium signaling pathway is related to progression and development of various cancers including lung adenocarcinoma [ 28 ], colorectal cancer [ 29 ], glioblastoma [ 30 ], breast cancer [ 31 ], and Burkitt lymphoma [ 32 ]. Calcium signaling pathway may play a key role in the progression and development of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ions play a vital role in muscle contraction, neuronal transmission, cell motility, cell growth or proliferation [ 24 27 ]. It has been reported that calcium signaling pathway is related to progression and development of various cancers including lung adenocarcinoma [ 28 ], colorectal cancer [ 29 ], glioblastoma [ 30 ], breast cancer [ 31 ], and Burkitt lymphoma [ 32 ]. Calcium signaling pathway may play a key role in the progression and development of AML.…”
Section: Discussionmentioning
confidence: 99%
“…To assist in visualizing the biological networks and integrating the data generated by the STRING database, the PPI networks were constructed and visualized using Cytoscape (version 3.3.0; ) ( 22 ). As the majority of the networks were scale-free, the hub genes were then selected with a connectivity degree >15 ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“… [ 333–336 ] Gene expression profiling of colorectal cancer, in comparison to normal colonic tissue, showed downregulation in cancer of genes associated with PD, AD, HD and oxidative phosphorylation. [ 337 ] Meta-analysis of transcriptomic data for AD, PD and schizophrenia, in relation to lung, prostate and colorectal cancer, showed opposite gene-expression changes between these two sets of diseases. [ 338 ] SIR, standard incidence rate; RR, relative risk; OR, odds ratio; HR, hazard ratio; ES, effect size; CI, confidence interval.…”
Section: Cancer Versus Neurodegenerative Diseasesmentioning
confidence: 99%